The role of sago (Metroxylon sp.) as staple food in supporting food security of household and community in Baloli Village, Masamba District, North Luwu Regency - Putri, Dwi Ahrisa; Nadja, Rahmawaty A.; Salman, Darmawan (Anjoro: International Journal of Agriculture and Business, 2020)
Sago is one of an endemic plant in Indonesia which produce starch as staple food in several area in Indonesia like Papua, Maluku, North Sulawesi, South Sulawesi, Southeast Sulawesi, Mentawai and West Sumatera. Sago has taken important role as one of carbohydrate source in Indonesia. This study aimed to know the role of sago in social or cultural, economic aspects and as a staple food in the level of household and community in Baloli Village, Masamba District, North Luwu Regency. The method used was survey method which was done by observation and interviews using questionnaires. The analysis used in this study was the analysis of the role of sago and food security and food consumption. The role of sago in terms of social or cultural aspects by qualitative and descriptive analysis of the economic analysis of sago farmers' income. The research proved that the role of social or cultural sago is viewed as a traditional crop that is consumed hereditary, there’s also some tradition and customs which maintain the value of life which is known as local wisdom, that’s reflected by the behavior in the society of Baloli Village particularly in sago cultivation and other plant parts such as leaves can also be utilized to craft into roofs and leftovers of the bark is used as fire wood and the pulp is used for animal feed. From the economic aspect, the biggest income of farmers who have their own sago palms and process them to sago starch despite the limited amount and it has not been able to support food security for household and community.